Implementation of Home Visite Program in Overcoming Student Learning Problems in SD Muhammadiyah 1 Pucanganom Sidoarjo - Lailatus Syifa’; Nurdyansyah Nurdyansyah; Nyong ETIS (Proceedings of The ICECRS, 2020)
The implementation of the home visit program at SD Muhammadiyah 1 Pucanganom Sidoarjo is use a qualitative study. The implementation of a home visit at SD Muhammadiyah 1 Pucanganom Sidoarjo consists of: 1) Planning / preparation, at this stage the teacher must know in advance the purpose of carrying out a home visit / home visit. 2) Implementation, so that the implementation of home visit remains focused on the objectives, the teacher must be able to pay attention to the time available and be able to make good communication to build parent's trust before digging student data. 3) Evaluation, so that the implementation of a home visit is beneficial for parents, teachers and students, the teacher must conduct an evaluation of the completeness and usefulness and commitment of parents in handling student learning problems both at home and at school. 4) Follow-up, After the teacher visits the student's home and knows the student's learning problem both at home and at school, then to deal with the problem the teacher must follow up. 5) Prepare a report on the results of the home visit, After getting the results of the home visit activity the teacher makes a report accompanied by photos and complete documentation and the results are conveyed to the principal. In home visit activities there are several supporting and inhibiting factors that are very influential including: family, school, and community environment. While the inhibiting factors include: Limited supervision of the school, awareness of students, the influence of television shows and gadgets. In implementing the home visit at SD Muhida there were also several obstacles so that the home visit encountered obstacles including: 1) the lack of follow-up in home visit activities. 2) The teacher does not support the home visit activities. 3) lack of support from parents. 4) less able to adjust the time.